A high-efficiency energy-saving and environment-friendly bio-based pigment preparation method
Patent Information
- Application Number
- CN202611081945.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-23
AI Technical Summary
但现有生物基颜料多通过动植物组织提取或微生物发酵获得,原料来源受限、生产工艺复杂,导致其色域覆盖范围窄、批次稳定性不足且成本居高不下
1、本发明采用冻融循环、热降解与球磨相结合的纯物理手段,以废旧染色纺织品为唯一原料,在不添加任何化学分散剂、偶联剂或有机溶剂的条件下,直接制备得到粒径小、分布集中且色泽完好的高品质纤维素粉末(生物基颜料)。本发明方法所制得的纤维素粉末粒径低至310 nm左右且分布范围极窄,结晶度从原棉织物的约85%降至约30%,同时最大热降解温度保持在300℃以上,远高于纺织品涂料印花常规干燥温度(80~100℃)与固化温度(150℃),兼具优异的反应活性与热加工适用性。本发明全流程绿色环保、环境足迹低,为废旧纺织品的高值化利用开辟了一条兼具显著经济效益与环保价值的全新路径。
Smart Images

Figure CN122960029A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid waste resource utilization and fine chemical preparation technology, specifically involving a method for preparing bio-based pigments from waste textiles based on cyclic freeze-thaw and thermal degradation pretreatment combined with ball milling process. Background Technology
[0002] Waste textiles have become one of the fastest-growing solid wastes globally, and their treatment and disposal are facing severe environmental and economic challenges. Under traditional landfill disposal, natural fibers degrade slowly in anaerobic environments, continuously producing leachate and greenhouse gases such as methane; while synthetic fibers are almost non-biodegradable and can remain in the environment for decades. Although incineration can achieve significant volume reduction, this process not only emits large amounts of toxic gases and dust such as carbon dioxide and dioxins, causing serious secondary pollution, but also fundamentally leads to the complete waste of fiber resources, running counter to the concept of a circular economy.
[0003] In terms of recycling technology, existing methods also have significant limitations. Mechanical recycling methods are generally only suitable for clean textile waste with a single component. For the large amount of complex post-consumer blended fabrics on the market, this method often only reduces them to low-value-added fillings or industrial rags, making it difficult to achieve high-value utilization. Chemical recycling methods attempt to reduce fibers to monomers through depolymerization reactions to achieve a closed-loop cycle. However, this technical route usually requires the use of strong acids, strong alkalis, or expensive ionic liquids and catalysts under high temperature and high pressure conditions. The process is lengthy, monomer separation and purification are difficult, and the cost of chemical reagent recovery is high, resulting in poor overall economic efficiency. The technical difficulty increases significantly, especially when selectively separating multi-component blended fabrics.
[0004] In recent years, the idea of directly converting waste textiles into pigment powder through physical pulverization has opened up a new direction for high-value utilization. However, existing direct mechanical pulverization methods face fundamental technical bottlenecks: the inherent flexibility and high toughness of fibers make it difficult to effectively refine them at room temperature, resulting in coarse powder particles with extremely wide particle size distribution; at the same time, due to the light scattering and masking effects of dyes inside the fibers, the powder has a dark tone, and its coloring power and brightness are far from meeting the basic requirements for pigment quality in industries such as coatings and inks. The incineration ash method completely removes all organic components from waste textiles at high temperatures, leaving only inorganic residues. This process completely destroys the organic pigment groups and functional structures contained in the fiber structure, resulting in ash with a single color and poor performance adjustability. Moreover, the process itself is energy-intensive and has high emissions, which contradicts the concept of green manufacturing. A few other studies have attempted to modify the surface of pulverized fiber powder through chemical grafting or coupling agent treatment to improve its dispersibility and compatibility. However, such methods introduce additional organic solvents and chemicals, the process steps are cumbersome, and they fail to fundamentally solve the two core problems of poor fiber particle morphology and effective pigment locking in dyed fibers.
[0005] In the field of bio-based pigments, the current market demand for products with good color saturation, excellent dispersion stability, renewable sources, and environmental friendliness is increasingly urgent. However, existing bio-based pigments are mostly obtained through extraction from animal and plant tissues or microbial fermentation, which limits the source of raw materials and complicates the production process, resulting in narrow color gamut coverage, insufficient batch stability, and high costs. The direct preparation of high-performance bio-based pigments from waste textiles—a waste material rich in color information and polymer structure—is currently a technological gap.
[0006] In conclusion, developing a highly efficient, energy-saving, environmentally friendly, and high-value-added method for recycling and reusing waste textiles has significant environmental and economic benefits. Summary of the Invention
[0007] To address the aforementioned technical problems, the purpose of this invention is to provide a method for recycling waste textiles. This method uses purely physical means to process waste textiles, thereby achieving the preparation of bio-based pigments with small particle size, narrow particle size distribution, good thermal and dispersion stability, and good dyeing effect.
[0008] To achieve the above objectives, this invention first provides a highly efficient, energy-saving, and environmentally friendly method for preparing bio-based pigments. This method employs a synergistic effect of cyclic freeze-thaw cycles and thermal degradation to treat fabrics, followed by ball milling to achieve efficient preparation of bio-based pigments. The specific preparation method includes the following steps: (1) Cyclic freeze-thaw treatment: After soaking the fabric in deionized water, it is taken out and subjected to freeze-thaw cycle treatment; (2) Thermal degradation treatment: After drying the fabric obtained in step (1), cut it into small pieces and carry out thermal degradation at a high temperature of 180~220℃; (3) Ball milling: The fabric obtained in step (2) is pulverized using a high-speed pulverizer and ball milled to obtain cellulose powder.
[0009] In one embodiment of the present invention, in step (1), the fabric is soaked for 20 to 36 hours, preferably 24 hours, and the number of freeze-thaw cycles is 1 to 7 times, preferably 2 to 6 times.
[0010] In one embodiment of the present invention, in step (1), the freezing temperature during the freeze-thaw cycle is -30~-60℃, the freezing time is 20~30h, preferably 24h, or freezing under liquid nitrogen conditions for 10min; thawing is performed at room temperature conditions of 15~35℃.
[0011] In one embodiment of the present invention, the fabric in step (1) is a cotton fabric or a linen fabric, preferably a dyed cotton fabric.
[0012] In one embodiment of the present invention, in step (2), drying is performed at 50~60°C for 20~30h, preferably at 50°C for 24h.
[0013] In one embodiment of the present invention, in step (2), the thermal degradation temperature is preferably 190~210 ℃ and the thermal degradation time is 30~70 min, preferably 40~60 min.
[0014] In one embodiment of the present invention, in step (3), the pulverization is performed by pulverizing the fabric into short fibers less than 3 mm at a rotation speed of 20,000 to 25,000 rpm.
[0015] In one embodiment of the present invention, in step (3), the ball milling speed is 500~800 rpm and the ball milling time is 2~8 h.
[0016] The present invention also provides a cellulose powder or bio-based pigment prepared according to the above method.
[0017] The present invention also provides the application of the above-mentioned cellulose powder or bio-based pigment in coating printing.
[0018] Beneficial effects: 1. This invention employs a purely physical method combining freeze-thaw cycles, thermal degradation, and ball milling. Using waste dyed textiles as the sole raw material, and without adding any chemical dispersants, coupling agents, or organic solvents, it directly prepares high-quality cellulose powder (bio-based pigment) with small particle size, concentrated distribution, and intact color. The cellulose powder obtained by this method has a particle size as low as approximately 310 nm and an extremely narrow distribution range. The crystallinity is reduced from approximately 85% of that in the original cotton fabric to approximately 30%. Simultaneously, the maximum thermal degradation temperature remains above 300℃, far exceeding the conventional drying temperature (80~100℃) and curing temperature (150℃) for textile pigment printing, exhibiting both excellent reactivity and thermal processing applicability. This invention is green and environmentally friendly throughout the entire process, with a low environmental footprint, opening up a new path for the high-value utilization of waste textiles that combines significant economic benefits with environmental value.
[0019] 2. This invention employs a combined pretreatment of fabrics using cyclic freeze-thaw cycles and thermal degradation, along with ball milling, to prepare cellulose powder with smaller particle size, narrower particle size distribution, better stability, and improved dyeing effect. The main mechanism is as follows: During multiple freeze-thaw cycles, the internal moisture of the fiber repeatedly crystallizes and melts. The volume expansion effect of the ice crystals causes repeated expansion and cracking of the fiber cell walls, forming numerous microcracks and structural defects at the microscopic level, initially disrupting the highly ordered aggregated structure of cellulose. Subsequently, dry heat treatment further intensifies the fiber's embrittlement, accompanied by the gentle breaking of some chemical bonds, effectively breaking down the fiber's original high toughness and high crystallinity barriers. Ultimately, the fiber, after freeze-thaw and heat treatment, transforms from its original high-toughness state into a uniformly embrittled state, causing the particle dissociation during subsequent ball milling to become primarily brittle dissociation. This allows for the efficient acquisition of ultrafine powder with small particle size and concentrated distribution without chemical assistance. At the same time, since the entire process does not involve high-temperature ablation or strong chemical reagents, the natural pigment groups contained inside the fiber are completely preserved and evenly distributed on the powder surface, giving the pigment products natural color characteristics.
[0020] 3. The bio-based pigment printing system prepared by this invention exhibits excellent color uniformity and printability. Simultaneously, the printed fabrics produced possess excellent color fastness, meeting the requirements for industrial applications. This invention uses waste textiles as the sole raw material throughout the entire process, eliminating the need for external chemical dispersants, coupling agents, or organic solvents. This fundamentally avoids the challenges of using and recycling strong acids, strong alkalis, and organic solvents in traditional chemical recycling methods. The process steps are simple, the operating conditions are mild, and it does not involve high temperature or high pressure, significantly reducing equipment investment and operating energy consumption. It also eliminates the risk of secondary pollution, making it a truly green, low-carbon, and recyclable technology with significant social benefits and promising prospects for industrial application. Attached Figure Description
[0021] Figure 1This is a particle size distribution diagram of the cellulose powder prepared in Example 1 of the present invention; Figure 2 The image shows the XRD pattern of the cellulose powder prepared in Example 1 of this invention. Figure 3 The TG and DTG images are of the cellulose powder prepared in Example 1 of this invention. Figure 4 This is a particle size distribution diagram of the cellulose powder prepared in Comparative Example 1 of the present invention; Figure 5 The image shows the XRD pattern of the cellulose powder prepared in Comparative Example 1 of this invention. Figure 6 The TG and DTG diagrams are shown for the cellulose powder prepared in Comparative Example 1 of this invention. Figure 7 This is a particle size distribution diagram of the cellulose powder prepared in Comparative Example 3 of the present invention; Figure 8 The image shows the XRD pattern of the cellulose powder prepared in Comparative Example 3 of this invention. Figure 9 The TG and DTG diagrams are shown for the cellulose powder prepared in Comparative Example 3 of this invention. Figure 10 This is a particle size distribution diagram of the cellulose powder prepared in Comparative Example 5 of the present invention; Figure 11 The image shows the XRD pattern of the cellulose powder prepared in Comparative Example 5 of this invention. Figure 12 The TG and DTG diagrams are shown for the cellulose powder prepared in Comparative Example 5 of this invention. Figure 13 This is a particle size distribution diagram of the cellulose powder prepared in Comparative Example 6 of the present invention; Figure 14 The image shows the XRD pattern of the cellulose powder prepared in Comparative Example 6 of this invention. Figure 15 The TG and DTG diagrams are shown for the cellulose powder prepared in Comparative Example 6 of this invention. Figure 16 The K / S curves for different positions of the printed fabric prepared in the application example of this invention are shown below. Figure 17 The reflectance spectra of different positions of the printed fabric prepared as an application example of the present invention. Detailed Implementation
[0022] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0023] The fabrics used in the embodiments and comparative examples of this invention are all dyed pure cotton fabrics.
[0024] Example 1 A method for preparing a bio-based pigment includes the following steps: (1) Soak the dyed cotton fabric in deionized water for 24 h, take it out and perform 5 cycles of freeze-thaw treatment. One freeze-thaw cycle is to freeze in a -40 ℃ refrigerator for 24 h, and then thaw at room temperature until completely melted. (2) After drying the cotton fabric obtained in step (1) at 50 °C for 24 h, cut it into 1 cm × 1 cm pieces, heat the small pieces of cotton fabric at 200 °C for 60 min, and take them out after the process is complete. (3) The cotton fabric that has undergone cyclic freeze-thaw and thermal degradation was initially crushed at 22,000 rpm using a high-speed pulverizer to crush it into short fibers less than 3 mm. The crushed cotton fabric was then transferred to a ball mill jar and ball-milled at 600 rpm for 4 h to obtain cellulose powder.
[0025] Figure 1 , Figure 2 and Figure 3 The particle size distribution, XRD pattern, and TG and DTG plots of the prepared cellulose powder, i.e., the bio-based pigment, are presented respectively. Figure 1 It can be seen that the cellulose powder prepared in Example 1 has a particle size of approximately 310 nm and a relatively concentrated distribution. Figure 2 It can be seen that the cellulose powder prepared in Example 1 still retains the type I cellulose structure, but the crystallinity is significantly reduced, from about 85% in the original cotton fabric to about 30%. Figure 3 It can be seen that the thermal stability of the cellulose powder prepared in Example 1 is lower than that of the original cotton fabric, but its maximum degradation temperature is still above 300 ℃. The degradation temperature range is much higher than the typical drying temperature (80~100 ℃) and curing temperature (150 ℃) commonly used in textile coating printing, which confirms its applicability as a bio-based pigment in actual printing processes.
[0026] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step (1), the number of freeze-thaw cycles is 1.
[0027] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that step (2) is omitted, and the fabric after the cyclic freeze-thaw treatment is directly crushed and ball-milled.
[0028] The properties of the fiber powder prepared in Comparative Example 1 are compared with those in Example 1 as follows: Figure 4 , Figure 5 and Figure 6 As shown. By Figure 4It can be seen that the particle size of the cellulose powder obtained in Comparative Example 1 is around 770 nm, which is significantly larger than the particle size of the cellulose powder prepared in Example 1, and the particle size distribution of the powder in Comparative Example 1 is also relatively wide. Figure 5 It can be seen that the cellulose powder prepared in Comparative Example 1 still retains the cellulose type I structure, and its crystallinity is close to that of the cellulose powder obtained in Example 1, both around 30%. Figure 6 It can be seen that the thermal stability of the cellulose powder prepared in Comparative Example 1 is slightly better than that in Example 1, and the maximum degradation temperature is slightly higher than that in Example 1, but the difference is small.
[0029] Comparative Example 2 underwent only freeze-thaw cycles, and the experiment found that the fabric in Comparative Example 2 was difficult to ball mill into powder.
[0030] As can be seen from Comparative Examples 1 and 2, the cellulose powder with small particle size, narrow particle size distribution, and better stability prepared by this invention is obtained through the combined effects of freeze-thaw cycle treatment and thermal degradation. The preparation principle is that during multiple freeze-thaw cycles, ice crystals repeatedly grow and melt in the fabric, causing the fabric to repeatedly expand and crack due to the action of ice crystals. During subsequent heat treatment, the fibers in the fabric become brittle, accompanied by the breakage of some bonds, resulting in a powder with a smaller particle size and narrower distribution after ball milling. The absence of any one of these steps will result in the inability to obtain a satisfactory cellulose powder. For example, in Comparative Example 1, reducing the number of freeze-thaw cycles significantly increased the particle size of the prepared cellulose powder, indicating that fewer freeze-thaw cycles cannot effectively promote fabric expansion and cracking. Similarly, in Comparative Example 2, the inability to prepare powder through ball milling without thermal degradation further illustrates the crucial role of thermal degradation.
[0031] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the thermal degradation temperature in step (2) is 180 °C.
[0032] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the thermal degradation temperature in step (2) is 230 °C.
[0033] The properties of the fiber powder prepared in Comparative Example 3 are compared with those in Example 1 as follows: Figure 7 , Figure 8 and Figure 9 As shown. By Figure 7 It can be seen that the particle size of the fiber powder obtained in Comparative Example 3 is around 420 nm, which is larger than the particle size of the cellulose powder prepared in Example 1, and the particle size distribution is also relatively wider. Figure 8 It can be seen that the cellulose powder prepared in Comparative Example 3 still retains the type I cellulose structure, but its crystallinity is slightly lower than that of the cellulose powder obtained in Example 1, at around 25%. Figure 9It can be seen that the thermal stability of the cellulose powder prepared in Comparative Example 3 is slightly better than that in Example 1, and the maximum degradation temperature is slightly higher than that in Example 1, but the difference is small.
[0034] Comparative Example 4: Due to the high thermal degradation temperature, the fabric underwent partial carbonization after thermal degradation, resulting in a significant difference in color between the prepared cellulose powder and the original fabric, making it unsuitable for use as a biomass pigment.
[0035] The experimental results of Comparative Examples 3 and 4 show that the thermal degradation temperature has a significant impact on the preparation of cellulose powder. When the thermal degradation temperature is low, the degradation of the fabric is insufficient, resulting in the inability to obtain powder with a sufficiently small particle size during subsequent ball milling. On the other hand, a high thermal degradation temperature will cause the fabric to carbonize, thereby affecting the color of the powder and its subsequent application effect.
[0036] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the thermal degradation time in step (2) is 30 min.
[0037] The properties of the fiber powder prepared in Comparative Example 5 are compared with those in Example 1 as follows: Figure 10 , Figure 11 and Figure 12 As shown. By Figure 10 It can be seen that the cellulose powder obtained in Comparative Example 4 has a particle size of approximately 480 nm, which is larger than the cellulose powder obtained in Example 1, and the particle size distribution is relatively wide, resulting in relatively poor powder size uniformity. Figure 11 It can be seen that the cellulose powder prepared in Comparative Example 4 still retains the cellulose type I structure, and its crystallinity is close to that of the cellulose powder obtained in Example 1, both around 30%. Figure 12 It can be seen that the thermal stability of the cellulose powder prepared in Comparative Example 4 is slightly better than that in Example 1, and the maximum degradation temperature is slightly higher than that in Example 1, but the difference is small.
[0038] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the thermal degradation time in step (2) is 70 min.
[0039] The properties of the fiber powder prepared in Comparative Example 6 are compared with those in Example 1 as follows: Figure 13 , Figure 14 and Figure 15 As shown. By Figure 13 It can be seen that the cellulose powder obtained in Comparative Example 6 has a particle size of approximately 230 nm, which is smaller than that of the cellulose powder obtained in Example 1, but the particle size distribution is relatively wide, and the uniformity of powder size is relatively poor. Furthermore, although the particle size decreased slightly after the time was extended to 70 min, the decrease was not significant. Figure 14It can be seen that the cellulose powder prepared in Comparative Example 6 still retains the cellulose type I structure, and its crystallinity is close to that of the cellulose powder obtained in Example 1, both around 30%. Figure 15 It can be seen that the thermal stability of the cellulose powder prepared in Comparative Example 6 is slightly better than that in Example 1, and the maximum degradation temperature is slightly higher than that in Example 1, but the difference is small. Considering energy consumption, efficiency, and printing requirements, this invention is still the optimal solution.
[0040] The results of Comparative Examples 5 and 6 show that the thermal degradation time also has a significant impact on the performance of cellulose powder. A shorter thermal degradation time cannot produce cellulose powder with a smaller particle size, while a longer thermal degradation time, although producing cellulose powder with a smaller particle size, results in poor particle size distribution uniformity, which also affects the application effect of cellulose powder in dyeing.
[0041] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that dry thermal degradation is replaced by hydrothermal treatment. Specifically, the product after step (1) is soaked in water and reacted in an oil bath at 200°C for 60 minutes.
[0042] Experimental results show that the dyed pure cotton fabric after hydrothermal treatment still retains high toughness and is difficult to ball mill into powder. This indicates that dry thermal degradation plays a decisive role in the preparation of bio-based pigments during the thermal degradation process.
[0043] Application examples In preparing the printing paste, 5% cellulose powder, 3% thickener, and 18% binder (all based on total paste mass) are dispersed in deionized water. After thorough homogenization, the prepared paste is applied to the fabric using a flatbed printing process. The printed fabric is then dried at 80°C for 5 minutes and cured at 150°C for 3-5 minutes.
[0044] The K / S values of printed fabrics were measured using a Datacolor 850 spectrophotometer (Datacolor, USA). Tests were conducted under standard conditions, using a D65 light source and a 10° viewing angle. To ensure accurate results, fabric samples were folded to prevent light penetration, and each sample was measured five times.
[0045] According to GB / T 3920-2008 standard, the samples were tested using an electric rubbing fastness tester (Darong Textile Instrument Co., Ltd., Wenzhou, China). The sample was fixed on the instrument with its length parallel to the direction of movement of the tester. A standard rubbing cloth (50 mm × 50 mm) was fixed to the rubbing head of the instrument, with the warp of the cloth at a 45° angle to the direction of movement of the tester. The sample was rubbed back and forth 10 times, with each reciprocating stroke being 10 cm. For the wet rubbing fastness test, the standard rubbing cloth was immersed in distilled water and then evenly pressed with a small roller until the liquid retention rate reached 100%. The wet rubbing test was repeated following the same procedure as the dry rubbing fastness test.
[0046] The color fastness to washing of printed fabrics was evaluated according to GB / T 3921-2008 "Textiles - Tests for Color Fastness - Color Fastness to Washing". The printed fabric samples were sewn together with multi-component fiber linings (wool, acrylic, polyester, nylon, cotton, viscose) and immersed in a soap solution containing 5 g / L standard soap flakes and 2 g / L anhydrous sodium carbonate at a liquor ratio of 50:1. The test was conducted at 60°C for 30 minutes. After treatment, the samples were removed, thoroughly rinsed with distilled water, and dried in air at a temperature not exceeding 60°C. Color change in the printed fabric and staining of the lining were assessed using a gray scale.
[0047] The results obtained from the printing application are as follows Figure 16 , Figure 17 And as shown in Tables 1 to 4.
[0048] Table 1. CIE L*a*b* chromaticity at different locations on printed fabrics
[0049] Table 2. Paired color difference matrix (ΔE) between different positions on the printed fabric
[0050] Table 3 Color fastness grades for rubbing of printed fabrics
[0051] Table 4. Color fastness grades for printed fabrics to soap washing
[0052] Depend on Figure 16 and Figure 17Apparent color depth (K / S) spectra and reflectance were collected at five randomly selected locations (AE) on the printed fabric. The spectral curves at all five locations highly overlapped, exhibiting a significant absorption maximum (lowest reflectance, highest K / S value) in the 530–550 nm wavelength range. This significant consistency between different sampling points strongly confirms the excellent color uniformity and printability of the formulated bio-based pigment system. Tables 1 and 2 further confirm the uniform deposition and excellent color consistency of the bio-based pigment. As shown in Table 1, the printed fabric exhibited significant color yield, with L* values at the five different locations remaining stable within a narrow range of 80.1–81.0, and a* values (redness) closely concentrated between 22.2–24.6. The highly consistent distribution of these chromaticity parameters on the substrate indicates that the bio-based pigment has excellent tinting strength on cellulose fibers. As shown in Table 2, the color difference matrix (ΔE) clearly confirms the minimal color differences between the sampling locations. The maximum deviation across the entire sampling area occurred between positions A and C, with a ΔE of only 2.5, well within the commercially acceptable tolerance range for textile color matching and printing uniformity. This convergence matrix of microscopic color differences strongly demonstrates that the bio-based pigment can achieve uniform dispersion and deposition on the fabric surface, thus imparting excellent surface effects to the printed products. Table 3 shows that the samples exhibit excellent rubbing fastness, reaching the highest grade of 5 for dry rubbing and 4 for wet rubbing. Furthermore, the washing fastness (Table 4) is also outstanding: the color change grade of the printed fabric is 4-5, and the staining grade of adjacent multi-component fiber linings (wool, acrylic, polyester, nylon, cotton, viscose) consistently reaches a high grade of 4-5 to 5. These excellent color fastness results indicate a strong physical and chemical adhesion between the pigment-binder network and the cellulose fibers, confirming the practical feasibility of this bio-based pigment in textile printing applications.
[0053] In summary, this invention employs a combination of cyclic freeze-thaw cycles and thermal degradation to treat cotton fabrics, and finally uses ball milling to prepare bio-based pigments. This method has advantages such as high efficiency, simple process, low cost, environmental friendliness, and energy saving, and is suitable for the high-value-added recycling of various waste fabrics.
[0054] The embodiments provided above are not intended to limit the scope of the invention, nor are the described steps intended to limit the order of execution. Any obvious modifications made to the invention by those skilled in the art based on existing common knowledge also fall within the scope of protection defined by the claims.
Claims
1. A method for preparing highly efficient, energy-saving, and environmentally friendly bio-based pigments, characterized in that, Includes the following steps: (1) Cyclic freeze-thaw treatment: After soaking the fabric in deionized water, it is taken out and subjected to freeze-thaw cycle treatment; (2) Thermal degradation treatment: After drying the fabric obtained in step (1), cut it into small pieces and carry out thermal degradation at a high temperature of 180~220℃; (3) Ball milling: The fabric obtained in step (2) is pulverized using a high-speed pulverizer and ball milled to obtain cellulose powder.
2. The preparation method according to claim 1, characterized in that, In step (1), the fabric is soaked for 20 to 36 hours and the freeze-thaw cycle is repeated 2 to 7 times.
3. The preparation method according to claim 1, characterized in that, In step (1), the freezing temperature during the freeze-thaw cycle is -30 to -60°C, the freezing time is 20 to 30 hours, or freezing is performed under liquid nitrogen conditions for 10 minutes; thawing is performed at 15 to 35°C.
4. The preparation method according to claim 1, characterized in that, The fabric mentioned in step (1) is a cotton fabric or a linen fabric.
5. The preparation method according to claim 1, characterized in that, In step (2), drying is carried out at 50~60℃ for 20~30h.
6. The preparation method according to claim 1, characterized in that, In step (2), the thermal degradation temperature is 190~210℃ and the thermal degradation time is 30~70 min.
7. The preparation method according to claim 1, characterized in that, In step (3), the pulverization is performed by pulverizing the fabric into short fibers less than 3 mm at a rotation speed of 20,000 to 25,000 rpm.
8. The preparation method according to claim 1, characterized in that, In step (3), the ball milling speed is 500~800 rpm and the ball milling time is 2~8 h.
9. Cellulose powder or bio-based pigment prepared by any one of claims 1 to 8.
10. The use of the cellulose powder or bio-based pigment of claim 9 in coating printing.